Silicon negative ion implantation induced vacancy defects in thermally grown SiO2 thin films. Issue 7 (3rd July 2020) - Vishwakarma, S. B.; Dubey, S. K.; Dubey, R. L.; Yadav, A.; Jadhav, V.; Bambole, V.; Sulania, I.; Kanjilal, D.; Devi, K. Devarani
ABSTRACT: Thermally grown SiO2 thin films on a silicon substrate implanted with 100 keV silicon negative ions with fluences varying from 1 × 10 15 to 2 × 10 17 ions cm −2 have been investigated using Electron spin resonance, Fourier transforms infrared and Photoluminescence techniques. ESR studies revealed the presence of non-bridging oxygen hole centers, E′-centers and Pb -centers at g-values 2.0087, 2.0052 and 2.0010, respectively. These vacancy defects were found to increase with respect to ion fluence. FTIR spectra showed rocking vibration mode, stretching mode, bending vibration mode, and asymmetrical stretching absorption bands at 460, 614, 800 and 1080 cm −1, respectively. The concentrations of Si–O and Si–Si bonds estimated from the absorption spectra were found to vary between 11.95 × 10 21 cm −3 and 5.20 × 10 21 cm −3 and between 5.90 × 10 21 cm −3 and 3.90 × 10 21 cm −3, respectively with an increase in the ion fluence. PL studies revealed the presence of vacancies related to non-bridging oxygen hole centers, which caused the light emission at a wavelength of 720 nm.